Respuesta :
Answer:
4
Step-by-step explanation:
-6g+36=12
-6g=12-36
-6g=-24
6g=24
g=24/6
g=4
Answer:
g= - 8
Step-by-step explanation:
Simplifying
-6g + -36 = 12
Reorder the terms:
-36 + -6g = 12
Solving
-36 + -6g = 12
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '36' to each side of the equation.
-36 + 36 + -6g = 12 + 36
Combine like terms: -36 + 36 = 0
0 + -6g = 12 + 36
-6g = 12 + 36
Combine like terms: 12 + 36 = 48
-6g = 48
Divide each side by '-6'.
g = -8
Simplifying
g = -8